Credibility and music´s effect as therapeutic kind in health - Karyne Cristine da Fonseca; Maria Alves Barbosa; Daniela Gonçalves Silva; Keylla Virgínia da Fonseca; Karina Machado Siqueira; Marcus Antônio de Souza (Revista Eletrônica de Enfermagem, 2006)
This article has as purpose to analise the professional´s music therapist´s perception about the credibility and approval of music therapy by their clients. It´s a qualitative research, developed in Goiânia-GO, between 2003, august and 2004, june. We verified that the professional´s majority noted their client´s credibility related to music capacity in transmitting pleasant sensations and its capacity to act in a efficient way on the healing process of some diseases. They too evidence that the music therapy needs to be published with more effectiveness for the population.